2013
DOI: 10.2166/wpt.2013.014
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate statistical analysis of the hydro-geochemical characteristics for Mining groundwater: a case study from Baishan mining, northern Anhui Province, China

Abstract: Major ions were analyzed for twenty five groundwater samples collected from diverse aquifer in Baishan mining, northern Anhui province, China. Conventional graphical and multivariate statistical approach were completed to identify the hydro-geochemical process and water-rock interaction, that be combined with the Cluster Analysis (CA) and Fisher discriminant analysis to recognize the sealed samples, the result showed: the diverse samples have vary ions inheriting from aquifer, samples collected from Sandstone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Multivariate technique has long been used for geological and hydrochemical data has long been described [16][17][18][19][20]. Factor analysis is the most commonly used statistical methods, which is used for classification, simplification of the data and finding the most important variables in the data set, or called as common factors.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate technique has long been used for geological and hydrochemical data has long been described [16][17][18][19][20]. Factor analysis is the most commonly used statistical methods, which is used for classification, simplification of the data and finding the most important variables in the data set, or called as common factors.…”
Section: Discussionmentioning
confidence: 99%
“…The property variations can be used to identify the water types and origins. Previous studies have shown that discriminant analysis is an efficient way to identify water sources and types (Chen et al 2013). The data from this study were analyzed using Fisher discriminant analysis (SPSS version 19) (IBM Corp. 2010), and the results are presented in Tables 3 and 4, and Figure 6.…”
Section: Fisher Discriminant Analysismentioning
confidence: 99%
“…These techniques were used for the identification of possible factors that influence the water systems and that cause variations in water quality (Wu and Kuo 2012). It has been widely used in water source identification including cluster analysis, factor analysis, discriminant analysis, fuzzy recognition, and back propagation (BP) neural networks (Gui and Chen 2007;Vasanthavigar et al 2012;Chen et al 2013;Chung et al 2015). Thivya et al (2013a) focused on the geochemical behavior of the groundwater samples with respect to lithology of Madurai region.…”
Section: Introductionmentioning
confidence: 99%